2016
DOI: 10.9734/ijpss/2016/24905
|View full text |Cite
|
Sign up to set email alerts
|

Inoculated Soybean Yields Response to Nitrogen and Phosphorus Application

Abstract: Inherent low soil nitrogen (N) and phosphorus (P) is one of the major hindrances of increased soybean productivity in Malawian soils. Although, inoculation of legumes with rhizobia, has been advocated for decades as a way of boosting leguminous crops' productivity through biological nitrogen fixation (BNF), the effectiveness of this strategy, has been low. An experiment was carried out to investigate the effect of the application of small doses of N and P to inoculated soybean. It was laid out in a complete bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Similarly application of 16 t FYM ha -1 + 60 kg S ha -1 on soybeanwheat cropping system produced maximum mean number of effective nodules per 5 plants (325) across 3 years, [43]. In agreement with this result, the highest number of effective nodule per plant (28% of the total nodules) over the control, where inoculation was combined with the application of 30 kg N ha -1 and 35 kg P ha -1 hence underlining the role played by phosphorus in nodule development and the role of starter N in soils which are low in N [53]. Likewise, integrated use of 50% RDF (10:30:20 kg NPK/ha) + 50% vermicompost (2.5 t/ha) obtained 19.21 number of effective nodules per plant in soybean [54].…”
Section: Nodulation and Growth Parameterssupporting
confidence: 77%
“…Similarly application of 16 t FYM ha -1 + 60 kg S ha -1 on soybeanwheat cropping system produced maximum mean number of effective nodules per 5 plants (325) across 3 years, [43]. In agreement with this result, the highest number of effective nodule per plant (28% of the total nodules) over the control, where inoculation was combined with the application of 30 kg N ha -1 and 35 kg P ha -1 hence underlining the role played by phosphorus in nodule development and the role of starter N in soils which are low in N [53]. Likewise, integrated use of 50% RDF (10:30:20 kg NPK/ha) + 50% vermicompost (2.5 t/ha) obtained 19.21 number of effective nodules per plant in soybean [54].…”
Section: Nodulation and Growth Parameterssupporting
confidence: 77%
“…Several studies have reported high nodule number when inoculant is applied together with P fertilizer. A high nodule number and increased BNF process was reported with inoculated soybean that received supplemental P fertilizer at Sumbrungu, Ghana (Akpalu, 2014) and Bvumbwe, Malawi (Phiri et al, 2016). Although the number of nodules and weight could be an indicator of high BNF process, it is not always the case unless the nodule activity is determined.…”
Section: Discussionmentioning
confidence: 99%
“…There are organizations involved in the development of soybean improved seed and accompanying agronomic practices such as inoculants, fertilizer regimes especially phosphorus and agroecologically suitable planting times. For instance, inoculation and P fertilizer application increased cowpea grain yield and above-ground plant dry matter at harvest in Mozambique (Kyei-Boahen et al, 2017) and soybean in locations of Kenya (Majengo et al, 2011), Ghana (Akpalu, 2014), Malawi (Phiri et al, 2016) and Rwanda (Rurangwa et al, 2018) among others. Majengo et al (2011) showed that inoculation of promiscuous medium-maturity soybean variety TGx1740-2F increased dry matter by 27% and average grain yield by 15-30% in Bungoma Kenya.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these challenges, soybean is the world's most traded oil seed and has the potential of being Africa's Cinderella crop (Kolawole, 2012;Lee et al, 2016). The demand for soybean is very high and increasing with the increasing population (Dlamini et al, 2013;Phiri et al, 2016;Ronner et al, 2016), however, yield is still fixed at an average of 1.1 t/ha for decades (Khojely et al, 2018). In South Africa, soybean is one of the country's main commodities and its production, promotion and processing has gained some priority in the country's industrial plans since 2010 (Dlamini et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, soybean is one of the country's main commodities and its production, promotion and processing has gained some priority in the country's industrial plans since 2010 (Dlamini et al, 2013). The area under soybean production has relatively increased to about 800,000 ha since 1903 when the crop was initially introduced to South Africa (Khojely et al, 2018;DALRRD, 2020), however, average yields are still lower than experimental yields due to drier climate and low fertility soils (Phiri et al, 2016;Ronner et al, 2016;Sithole et al, 2016). For optimal yields, soybean requires between 15 and 18 mg/kg P in the soil (FERTASA, 2016).…”
Section: Introductionmentioning
confidence: 99%